1982
DOI: 10.1259/0007-1285-55-649-42
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotection of mouse skin by WR-2721 in single and fractionated treatments

Abstract: The radioprotective action of WR-2721 on mouse skin has been studied using single doses, two and five fractions. Significant radioprotection was observed with 200-500 mg/kg, in animals breathing air or oxygen at the time of irradiation. The degree of radioprotection increased with increasing dose, and was significantly greater in air than in oxygen, especially at low drug doses. Cumulative drug toxicity limited the fractionated treatments to lower drug doses, but the protection observed was similar to that see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In long-term studies, Am has a radiation dose modification factor (DMF) greater than 2, meaning that a 15-Gy salivary gland dose can be mitigated to an equivalent of <7.5 Gy (Sodicoff et al 1978). DMF is a function of amifostine concentration, which we have maximized through local delivery (Stewart and Rojas 1982). It has been shown that saliva flow from the rat SMG at 3 mo following doses <7.5 Gy is not significantly lower than baseline (Nagler et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In long-term studies, Am has a radiation dose modification factor (DMF) greater than 2, meaning that a 15-Gy salivary gland dose can be mitigated to an equivalent of <7.5 Gy (Sodicoff et al 1978). DMF is a function of amifostine concentration, which we have maximized through local delivery (Stewart and Rojas 1982). It has been shown that saliva flow from the rat SMG at 3 mo following doses <7.5 Gy is not significantly lower than baseline (Nagler et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Yuhas and Storer [4] subsequently showed that pretreatment with amifostine effectively protects normal tissues from the toxicities of therapeutic radiation without protecting tumors. Amifostine was shown to protect irradiated gastrointestinal mucosal tissue [5], parotid gland [6,7,8,9], kidney [10], bone marrow [11], spermatogenetic cells [12,13], skin [14], hair follicles [15] and lung [16] in mice.…”
Section: Introductionmentioning
confidence: 99%
“…5-hydroxytryptamine, catecholamine and acetylcholine (24,25,42,8,59,60,37,38,6,57). Studies on the chemical protection of the brain in terms of DNA, RNA and protein contents against ionizing radiation have received little attention (11,51,32,39).…”
mentioning
confidence: 99%